PENGARUH LAMA PERENDAMAN PADA PENGOLAHAN TEPUNG SALAK - Dwi Ari Cahyani; Lukmanul Hakim (Jurnal Ilmiah Media Agrosains, 2016)
Salacca is one of the leading commodity products Banjarnegara. Bark flour processing is expected to increase the diversification of products processed bark. This research aims to study the processing of bark bark into flour with a variety of soaking and drying treatments with raw materials barking pondoh nglumut that are characteristic of the local district Banjarnegara. Research applying experimental research methods. The experimental design used was a completely randomized design with 3 replications. Further follow-up test was used to determine whether there is a real difference between the various treatments using DMRT. Results of DMRT done soaking solution of 1,5 g of sodium metabisulphite for 10 min weight of flour produced 64,33 g, soaking solution of sodium metabisulfite 2 g for 10 min weight of flour produced 65,20 g, 1 immersion solution of sodium metabisulfite g for 20 min weight of flour produced at 64,33 g.